Real-world effectiveness of Fertistartkit® treatment in women undergoing ART in French clinical practice: a retrospective multicentre study. Issue 4 (April 2020) - Languille, Solène; Massin, Nathalie; Santulli, Pietro; Ozanon, Christophe; Kazdar, Nadia; Lechat, Xenia; Soriano, Emilie; Frantz-Blancpain, Sandrine; Callec, Ronan; Guerif, Fabrice; Anahory, Tal; Rongières, Catherine; et al.
Abstract: Research question: What is the real-world effectiveness of Fertistartkit® in women undergoing assisted reproductive technology (ART)? Design: Retrospective cohort study including anonymized data of women undergoing ovarian stimulation for ART with Fertistartkit between April 2016 and November 2017 and follow-up of clinical outcomes up to February 2018. Data were collected from the electronic patient databases of 12 French ART centres. The main outcome was number of oocytes retrieved. All data were categorized according to female age (<25, 25–29, 30–34, 35–37, 38–39 and >39 years). Results: A total of 1006 cycles from 914 women treated with Fertistartkit were included. At the time of first ovarian stimulation in the study, women were 34.9 ± 5.0 years old, with a median body mass index of 22.7 kg/m². Couples had been infertile for more than 4 years, with all patterns of causes of infertility. Ovarian stimulation was started with a median dose of 300 IU (interquartile range [IQR]: 150–300 IU) of Fertistartkit for 10 days (IQR: 9–11 days), so a median total dose of 2700 IU (IQR: 1800–3300 IU). The mean number of oocytes retrieved per cycle was 9.5 ± 6.8, and the mean number of mature oocytes per cycle was 7.4 ± 5.5. The obtained ongoing pregnancy per started cycle was 26.0% (95% confidence interval [CI]: 24.1–27.9) and the obtained ongoing pregnancy per puncture was 27.0% (95% CI: 25.0–29.0). Conclusions: This is the first cohort to describe Fertistartkit treatment management in real-life conditions. The real-world data show that Fertistartkit is an effective option for ovarian stimulation.